The Lived Experiences, Perceptions, and Considerations of Patients After Operable Lung Cancer Concerning Nonparticipation in a Randomized Clinical Rehabilitation Trial. (April 2020) - Schoenau, Mai Nanna; Hansen, Mette; Ulvestad, Sigrid; Sommer, Maja Schick; Pedersen, Jesper Holst; Missel, Malene
The purpose of this study was to explore the lived experiences, perceptions, and considerations of individuals who declined participation in a randomized clinical trial involving exercise rehabilitation after surgery for lung cancer. An interpretive phenomenological approach was applied comprising interviews with 15 individuals who did not wish to participate in the trial. The findings shed light on a discrepancy between their freedom to act and make decisions and the limitations of having to act in a certain way. The participants found themselves in a gray area between a healthy life and a good life, as influenced by societal norms and taking responsibility for one's own health and rehabilitation. When including patients in rehabilitation after lung cancer, having insight into the underlying narrative on values and the good life, priorities in daily life, social context and the norms embedded in people's self-understanding is crucial.